Predictive validity of the Braden Scale, Norton Scale, and Waterlow Scale in the Czech Republic - Šateková, Lenka; Žiaková, Katarína; Zeleníková, Renáta (International journal of nursing practice, 2017)
The aim of this study was to determine the predictive validity of the Braden, Norton, and Waterlow scales in 2 long-term care departments in the Czech Republic. Assessing the risk for developing pressure ulcers is the first step in their prevention. At present, many scales are used in clinical practice, but most of them have not been properly validated yet (for example, the Modified Norton Scale in the Czech Republic). In the Czech Republic, only the Braden Scale has been validated so far. This is a prospective comparative instrument testing study. A random sample of 123 patients was recruited. The predictive validity of the pressure ulcer risk assessment scales was evaluated based on sensitivity, specificity, positive and negative predictive values, and the area under the receiver operating characteristic curve. The data were collected from April to August 2014. In the present study, the best predictive validity values were observed for the Norton Scale, followed by the Braden Scale and the Waterlow Scale, in that order. We recommended that the above 3 pressure ulcer risk assessment scales continue to be evaluated in the Czech clinical setting.
Keywords: senioři; Waterlow Scale; senioři nad 80 let; Long-Term Care; Norton Scale; Predictive Value of Tests; Česká republika; Risk Assessment; Middle Aged; ROC Curve; mužské pohlaví; prediktivní hodnota testů; Prospective Studies; Adult; Czech Republic; ROC křivka; Aged, 80 and over; Pressure Ulcer; ženské pohlaví; hodnocení rizik; Humans; prospektivní studie; pressure ulcers; predictive validity; lidé středního věku; dekubity; rizikové faktory; nursing; dospělí; Female; dlouhodobá péče; Aged; Risk Factors; Braden Scale; výzkumný projekt; Research Design; lidé; Male